Pelatihan Pemanfaatan AI Generatif Dalam Membuat Media Pembelajaran Interaktif Bagi Guru Di MTs YPKP Sentani - Manalu, Etty Octaviani; Pujowati, Maya; Suwarningsih, Tri (Universitas Cenderawasih, 2024)
The use of technology in the world of education is increasingly developing, one of which is the use of generative Artificial Intelligence (AI) to support interactive learning. This Community Service (PkM) aims to train MTs teachers in utilizing generative AI, such as ChatGPT, Canva AI, and Gemini in creating interesting and innovative learning media. Activity methods include socialization, interactive workshops, direct practice, and mentoring. The results of the activity show that teachers are very capable of using generative AI technology, namely with a percentage of 85% of teachers succeeding in creating text-based teaching materials using GPT chat, 90% of teachers being able to create interactive visual media using Canva AI and 80% of teachers being able to produce relevant illustrative images. using Gemini. With this increase in competency, it is hoped that learning at MTs will become more creative, interactive, and in line with the needs of the digital era